Analysis of Financial Inclusion Toward Poverty and Income Inequality - Ikrima Zaleda Zia; P. Eko Prasetyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
The objective of this study is to analyze the relationship and the influence of financial inclusion toward poverty alleviation and income inequality in Indonesia. The analysis methods in this study were Index Inclusion and regression-correlation of panel data. The variable of financial inclusion was obtained from Index of Financial Inclusion (IFI) value measured by dimensions; banking penetration, banking services availability, and the use of banking services. The data was time series from 2014-2016 and cross section from 33 provinces in Indonesia obtained from Bank Indonesia, Financial Service Authority, and Central Bureau Statistics. The results showed; (1) most provinces in Indonesia had moderate financial inclusion level, (2) financial inclusion had a negative and significant relationship and influence toward poverty. (3) financial inclusion had a positive and not significant relationship with income inequality, but it had a negative and significant influence toward income inequality. It means that financial inclusion can reduce poverty, but it has not been able to reduce the economic gap of society well.